Mortality of a cohort in a polyamide-polyester factory in Lyon: a further follow up. Issue 9 (September 1989) - Hours, M; Cardis, E; Marciniak, A; Quelin, P; Fabry, J
Abstract : In 1981-2 a retrospective study was undertaken in a polyamide-polyester factory in Lyon, France, to evaluate the effect of exposure to phthalates, nickel catalysers, and other chemicals in the work environment. The present paper reports the results of the follow up of this cohort up to July 1986. A slightly increased risk of cancers, in particular of the lung (44 cases), marginally related to exposure category but not significantly related to duration of exposure was found. The excess of skin cancers noted previously has disappeared, whereas an excess of cases of bladder cancer (based on seven cases) may be noted, mainly among nylon workers. The cohort is still young, however, and a continued follow up is likely to yield important information about the potential hazards associated with the nylon and tergal polymer industry.